Predictive Value of Peri-Coronary Fat Attenuation Index in Elderly Non-ST-Elevation Myocardial Infarction and Its Correlation with Platelet to Lymphocyte Ratio - Yanglei Li; Chen Wang; Qinyue Wang; Siqi Li; Junchao Yang; Hanqin Pan; Ming Li; Xinkai Qu; Yiran Qin; Chunwei Ma; Lin Qi; Mingxuan Li; et al. (BMC Cardiovascular Disorders)
Abstract Background Inflammatory mediators and immune activation can intensify the inflammatory response within atherosclerotic plaques, increasing the risk of plaque rupture and thrombosis. This study aims to compare peri-coronary adipose tissue fat attenuation index (PCAT-FAI) and platelet-to-lymphocyte ratio (PLR) between NSTEMI and SA patients, and explore their combined predictive ability for NSTEMI. Patients and methods : The study included 52 NSTEMI patients aged 65 and older who underwent both CCTA and CAG from January 2020 to December 2022, alongside 52 gender- and age-matched SA patients, and 52 control patients. PCAT-volume and PCAT-FAI were measured using Siemens VB20.0, and PLR was calculated from peripheral blood tests. Results Among 156 patients, NSTEMI patients had significantly higher PCAT volume (12.13 ± 5.32 mm³) compared to SA (8.39 ± 4.10 mm³, p < 0.001) and controls (6.28 ± 3.40 mm³, p < 0.001). They also had higher PCAT-FAI (-76.28 ± 5.33 HU) than SA (-82.87 ± 6.19 HU, p < 0.001) and controls (-84.19 ± 5.74 HU, p < 0.001). PLR was higher in NSTEMI patients (178.27 ± 107.18) compared to SA (115.54 ± 45.28, p = 0.002) and controls (116.09 ± 38.09, p = 0.006), with no significant difference between SA and controls (p = 1.000). PCAT-FAI correlated with PLR (CC: 0.298; P < 0.01). Combining PLR and PCAT-FAI predicted NSTEMI with an AUC of 0.799 (95% CI, 0.715–0.883). Conclusion Higher PCAT-FAI and PLR in NSTEMI patients highlight the role of adipose tissue inflammation and thrombosis in coronary artery disease progression. Combined assessment of PCAT-FAI and PLR has potential value in predicting the adverse progression of atherosclerotic plaques.